2017
DOI: 10.1155/2017/9418305
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Participatory Research Approach to Understand Urban Latino Parent’s Oral Health Knowledge and Beliefs

Abstract: The aim of this study is to describe oral health knowledge, behaviors, and beliefs of Latino parents with children under the ages of 6 years and to conduct a needs assessment with Latino families to better understand the challenges in maintaining oral health for their children. The investigator collaborated with a community serving the organization to recruit Latino primary caregivers for focus groups interviews and 30 primary caregivers were recruited. The focus groups data was transcribed and analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 13 publications
0
16
0
7
Order By: Relevance
“…Therefore, dental teams should teach caregivers the principles of quality oral care, which are necessary for their own and their children's oral health. A previous study reported that Latino caregivers mentioned several barriers in taking care of their children's oral health; for example, they expect dental professionals to demonstrate how to perform quality oral self‐care …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, dental teams should teach caregivers the principles of quality oral care, which are necessary for their own and their children's oral health. A previous study reported that Latino caregivers mentioned several barriers in taking care of their children's oral health; for example, they expect dental professionals to demonstrate how to perform quality oral self‐care …”
Section: Discussionmentioning
confidence: 99%
“…The public health implication of the present work was to acquire necessary information, understand the needs of this population, and prepare for designing culturally appropriate oral health education program for Mexican caregivers. A successful preventive program could lead to a higher sense of parental self‐efficacy, and subsequently, the establishment of oral health maintenance practices for the family …”
Section: Introductionmentioning
confidence: 99%
“…Caregivers are already aware of general topics regarding children's oral health, such as the fact that the consumption of sugary food causes caries and that teeth should be cleaned; however, knowledge limitations are seen when speaking about specific topics such as the bacterial origin of caries, the use of fluoride toothpaste, parental supervision during tooth brushing and the importance of an early dental appointment [21][22][23][24][25] The best way to control ECC is to give caregivers oral health education before the baby turns one year of age, so they can value the impor-…”
Section: Introductionmentioning
confidence: 99%
“…Los padres de familia están al tanto de cuestiones generales sobre la salud bucal de los niños, como el consumo de alimentos altos en azúcar es el causante de las caries y que los dientes deben ser higienizados; pero en temas específicos como el origen bacteriano de la caries, uso del dentífrico fluorado, la supervisión del cepillado por los padres y la importancia de la visita odontológica a temprana edad; se observan limitaciones de conocimiento [21][22][23][24][25] La mejor forma de controlar la Caries de la Infancia Temprana es la educación odontológica a los padres o cuidadores antes del primer año de vida con el objetivo que ellos valoren la importancia de mantener una buena salud bucal en niños de esa edad 26 . La aplicación de Educación para la Salud requiere de un modelo que modifique el comportamiento de los individuos y poblaciones para mejorar su salud.…”
Section: Introductionunclassified
See 1 more Smart Citation